Inovasi dan Retensi Fonologis Proto Bahasa Melayu pada Bahasa Melayu Riau Dialek Pesisir - NFN Ubaidillah; NFN Norlaili (Ranah: Jurnal Kajian Bahasa, 2020)
Malay is one of languages that has many speakers. One area of Malay language speakers is Riau. Riau Malay language has few differences in the lexicons, so that it can be said as a sub-dialect. Therefore, it is important to study further about the communication language of Riau Malay, especially Riau Malay coastal dialect used in Tembilahan Sub-district by using diachronic study. This study aims to describe the reflexes of Malay protol-anguage phonemes of Riau Malay coastal dialect in Tembilahan Sub-district which is then followed by making the rules of changing Malay proto-language phonemes of Riau Malay coastal dialect in Tembilahan Sub-district and the rules for retention forms of its phonemes. The method used in this study is a qualitative deductive method that applies top-down reconstruction technique. The results obtained in this study are that Riau Malay coastal dialect used in Tembilahan Sub-district has some innovation rules, both in the forms of primary innovations and secondary innovations. The primary innovations have three types of innovations, namely substitution, split, and merger, while secondary innovations, consisting of lenition, fortition, metathesis, syncope, prothesis, and paragoge. AbstrakBahasa Melayu merupakan salah satu bahasa dunia yang memiliki banyak pengguna. Salah satu daerah pengguna bahasa melayu adalah Riau. Bahasa Melayu Riau memiliki sedikit perbedaan-perbedaan dalam leksikonnya sehingga bisa dikatakan sebagai subdialek. Oleh karena itu, perlu dilakukan penelitian lebih jauh mengenai bahasa komunikasi Melayu Riau, tepatnya bahasa Melayu Riau dialek Pesisir yang digunakan di Kecamatan Tembilahan dengan menggunakan kajian diakronis. Penelitian ini bertujuan untuk mengetahui gambaran refleks fonem-fonem protobahasa Melayu pada bahasa Melayu Riau dialek Pesisir di Kecamatan Tembilahan yang kemudian dilanjutkan dengan membuat kaidah-kaidah perubahan fonem-fonem protobahasa Melayu pada bahasa Melayu Riau dialek Pesisir di Kecamatan Tembilahan berikut kaidah retensi fonem-fonemnya. Metode yang digunakan dalam penelitian ini adalah metode deduktif kualitatif yang menerapkan teknik rekonstruksi dari atas ke bawah (top-down reconstruction). Hasil yang diperoleh dalam penelitian ini adalah terdapat kaidah inovasi-inovasi Melayu Riau dialek pesisir yang digunakan di Kecamatan Tembilahan, baik yang berupa inovasi primer maupun inovasi sekunder. Adapun inovasi primer, memiliki tiga jenis inovasi, yaitu substitusi, split, dan merger, sedangkan inovasi sekunder, terdiri atas lenisi, fortisi, metatesis, sinkope, protesis, dan  paragog.